PENGARUH KUALITAS KEHIDUPAN KERJA TERHADAP KEPUASAN KERJA MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI PADA BANK MANDIRI KOTA KEDIRI - Nimas Lupita Regie Andriwardhaya; Eka Askafi; Abu Talkah (Commodities, Journal of Economic and Business, 2021)
In an organization there are important factors that are very influential, one of them is human resources (HR) who operate all other resources in an organization. An organization needs to develop the best ways to manage HR so that it can be used optimally to increase employee’s job satisfaction with the organization. The objectives of this study are (1) to analyze the influence of the work life quality on job satisfaction of employees. (2) Analyze the influence of the work life quality on organizational commitment. (3) Analyzing the effect of organizational commitment on employee’s job satisfaction. (4) Analyzing the influence of the work life quality on job satisfaction with organizational commitment as a mediating variable for employees. This type of research is a quantitative study. Hypothesis testing using Structural Equation Modeling (SEM). This research was conducted at Bank Mandiri Kota Kediri with a sample of 140 employees. The results of this study are (1) work life Quality has no significant effect on job satisfaction of employees of Mandiri Bank (2) work life Quality has a significant and positive effect on organizational commitment to Mandiri Bank employees (3) Organizational commitment has a significant and positive effect on job satisfaction for employees of Mandiri Bank (4) Organizational commitment mediate the influence of the work life quality on job satisfaction of employees of Mandiri Bank Kediri city.